To solve the equation \(\frac{3}{7}x + \frac{6}{7} - 2x = 4\), we can follow these steps:
-
Combine like terms: First, rewrite \(2x\) as \(\frac{14}{7}x\) so that we can combine it with \(\frac{3}{7}x\).
\[ \frac{3}{7}x - \frac{14}{7}x + \frac{6}{7} = 4 \]
This simplifies to:
\[ \frac{3 - 14}{7}x + \frac{6}{7} = 4 \]
\[ -\frac{11}{7}x + \frac{6}{7} = 4 \]
-
Isolate the \(x\) term: Subtract \(\frac{6}{7}\) from both sides.
\[ -\frac{11}{7}x = 4 - \frac{6}{7} \]
Convert \(4\) to a fraction with a denominator of \(7\):
\[ 4 = \frac{28}{7} \]
So,
\[ 4 - \frac{6}{7} = \frac{28}{7} - \frac{6}{7} = \frac{22}{7} \]
Therefore, we have:
\[ -\frac{11}{7}x = \frac{22}{7} \]
-
Solve for \(x\): To isolate \(x\), we can multiply both sides by \(-\frac{7}{11}\):
\[ x = \frac{22}{7} \cdot -\frac{7}{11} \]
The \(\frac{7}{7}\) cancels out:
\[ x = -\frac{22}{11} = -2 \]
Thus, the solution to the equation is:
\(\boxed{-2}\)